The unexpected Mrs. Pollifax [compact disc, unabridged] - Gilman, Dorothy, 1923-2012 (Recorded Books, 1989)
A widowed matron decides to pursue her lifelong desire to be a spy, finds herself useful to the CIA, and successfully completes an assignment which takes her from New Jersey to Mexico City to Albania.